Konsep Harta dan Kepemilikan Dalam Islam - Maryam Batubara; Hamdani; Raisa Aulia Rahma; Ilham Akbar Lubis (JOURNAL SAINS STUDENT RESEARCH, 2023)
In order for mankind to sustain themselves and effectively worship Allah swt, they must have property. However, the Qur'an cautions that property must be acquired in accordance with Islamic law and utilized in locations where righteousness is mandated by Islamic law. One idea that Islamic law has established to address the issue of property is that, rather of having explicit laws outlined in the Quran and Hadis, broad guidelines are presented here that every anyone attempting to get property must abide by. Islamic law mandates that the following guidelines be followed while purchasing and maintaining property: 1) Acquired and held property does not belong to the category of filthy and hazardous to humans; 2) The means of obtaining the property are humane and include the parties buying and selling the property, blessing each other, and keeping their word when entering into a covenant; 3) Islamic law outlines basic requirements that must be taken into consideration for the party with the authority to handle property, including a minimum age of 18 years and the possession of a ruysd (smart) characteristic, which is the capacity to handle property in accordance with Islamic law. Property may be appreciated and benefit humans by upholding human bodily and spiritual integrity and by adhering to all previously specified guidelines (mukallaf). The aim of the research carried out is to find out how to actually manage property and ownership properly and in accordance with Islamic law. Apart from that, we also need to better understand how property and ownership is actually distributed or distributed to those who are entitled to receive it.